Re-irradiation in head and neck cancers: an Indian tertiary cancer centre experience. Issue 11 (November 2014) - Mallick, S; Gandhi, A K; Joshi, N P; Pandit, S; Bhasker, S; Sharma, A; Thakar, A; Mohanti, B K
Abstract Objective: To explore the treatment outcomes of patients treated with re-irradiation for recurrent or second primary head and neck cancer. Method: An analysis was performed of 79 head and neck cancer patients who underwent re-irradiation for second primaries or recurrent disease from January 1999 to December 2011. Results: Median time from previous radiation to re-irradiation for second primary or recurrence was 53.6 months (range, 2.7–454.7 months). Median age at diagnosis of first primary was 54 years. Median re-irradiation dose was 45 Gy (range, 45–60 Gy). Acute grade 3 or worse toxicity was seen in 30 per cent of patients. Median progression-free survival for recurrent disease was 15.0 months (95 per cent confidence interval, 8.33–21.66). The following factors had a statistically significant, positive impact on progression-free survival: patient age of less than 50 years (median progression-free survival was 29.43, vs 13.9 months for those aged 50 years or older; p = 0.004) and disease-free interval of 2 years or more (median progression-free survival was 51.66, vs 13.9 months for those with less than 2 years disease-free interval). Conclusion: Re-irradiation of second primaries or recurrences of head and neck cancers with moderate radiation doses yields acceptable progression-free survival and morbidity rates.